THE RELATIONSHIP BETWEEN GENDER, HISTORY OF ANKLE SPRAIN, AND ANKLE STABILITY WITH ANKLE SPRAIN STATUS - Zhafira Faruhasa (The Indonesian Journal of Public Health, 2020)
Injuries can occur as a result of various activities, which of them is a sport. In 2017, basketball was a sport that produced the highest prevalence of injury incidence in the United States at 15.77%. Athletes who have ankle sprain are 20-40% more likely to experience chronic ankle instability. This study analyzed the relationship between gender, history of ankle sprain, and ankle stability with ankle sprain status in basketball athletes of Universitas Airlangga Surabaya. This study was analytical-observational research using a cross-sectional design. The research population was basketball athletes who were members of the basketball club of Universitas Airlangga, and finally there were 23 respondents selected as the research samples. The sample selection used the accidental sampling technique. The results of chi-square test (α = 0.05) indicate that there was a relationship between the previous history of ankle sprain (p = 0.002; RR = 9.1) and ankle stability with ankle sprain status (p = 0.013; RR = 6.), but gender had no relationship with ankle sprain status (p = 0.435; RR = 1.6). It concludes that the history of ankle sprain injury and ankle stability were related to ankle sprain status, but gender was not related to it. Keywords: gender, history of ankle sprain, ankle stability, ankle sprain